Do eco-friendly attributes of diarrhoea medicines matter? Its influence on green purchase intention - Wiwik Prihartanti; Bambang Purwoko; Erlyna Hidyantari; Hardiono Hardiono; Agus Rahmanto (Enrichment : Journal of Management, 2023)
The purpose of this study is to analysis the effect of environmental concern, environmental attitude and environmental knowledge on green purchase intention of environmentally friendly herbal medicines. The variables of this study include environmental knowledge, environmental concern and environmental attitude which are called independent variables, while the dependent variable is green purchase intention. Data analysis using Multiple Linear Regression with PLS software. The data sources in this study are primary data and secondary data, where primary data uses a questionnaire method data collection method distributed online and the sample totalled 91. This study produces findings that green purchase intention of environmentally friendly herbal medicines is influenced by environmental concern, environmental attitude and environmental knowledge